A review on qualification and certification for metal additive manufacturing. Issue 2 (3rd April 2022) - Chen, Ze; Han, Changjun; Gao, Ming; Kandukuri, Sastry Yagnanna; Zhou, Kun
ABSTRACT: Metal additive manufacturing (AM) has tremendous potential for manufacturing geometrically complex metallic products with freedom of design and desirable performance. Qualification and certification are critical to ensuring the successful adoption of metal AM by various sectors and accelerating the standardisation progress. This article provides a comprehensive review on the status of standardisation and challenges for the qualification and certification of metal AM, which is a timely summary to bridge the readiness gap between metal AM technologies developed at academia and industry. It begins with introducing fundamentals of metal AM qualification and certification. Thereafter, the status of standards, rules, and regulations developed by international organisations and communities is summarised and discussed. The challenges are then addressed, including the qualification and certification process, materials, process reliability and repeatability, post-processing, data, and standards and protocols. Finally, the conclusion and future outlook are drawn to provide guidance for future research and development.